2022
DOI: 10.1177/23800844221086205
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Toothbrushing in Indigenous and Non-Indigenous Australian Children

Abstract: Introduction: Dental caries in children is a multifactorial and complex condition. Toothbrushing helps maintain good oral hygiene and delivers fluoride. However, determinants of toothbrushing could vary based on Indigenous status. Objective: This study aimed to assess the association between socioeconomic status and adequate toothbrushing practice (brushing twice or more a day) in Indigenous and non-Indigenous Australian children. Methods: Data were acquired from the National Child Oral Health Survey (NCOHS) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
5
1
1
Order By: Relevance
“…In the present study the estimated percentage of brushing frequency was four times more in females than males and was in accordance with a study carried out by Farsi et al 16 . The percentage of patients with bleeding gums was almost equal in both the genders with a mere difference of 0.2% in contrast to a study carried out among undergraduate students from King Saud University, College of Dentistry where gingival bleeding was more in females as compared to the males 17 . Halitosis is a common feature of poor oral hygiene 16 and that was clearly evident in this study with a higher ration in male than female as reported in another study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In the present study the estimated percentage of brushing frequency was four times more in females than males and was in accordance with a study carried out by Farsi et al 16 . The percentage of patients with bleeding gums was almost equal in both the genders with a mere difference of 0.2% in contrast to a study carried out among undergraduate students from King Saud University, College of Dentistry where gingival bleeding was more in females as compared to the males 17 . Halitosis is a common feature of poor oral hygiene 16 and that was clearly evident in this study with a higher ration in male than female as reported in another study.…”
Section: Discussioncontrasting
confidence: 75%
“…Halitosis is a common feature of poor oral hygiene 16 and that was clearly evident in this study with a higher ration in male than female as reported in another study. 17 According to the results of our study gingival recession was encountered in 77% male and 12% female, a higher number of males might be accredited to poor oral Hygiene maintenance and incorporating the habit of smoking as there is a positive relationship between gingival recession and smoking.…”
Section: Discussionmentioning
confidence: 56%
“…For Indigenous children, those with 1 parent born outside Australia were more likely to brush more frequently. These findings indicate that cultural differences that may also have an impact on oral health and disease exist within apparently homogeneous communities (Fernando et al 2023).…”
mentioning
confidence: 87%
“…Also in this issue, Fernando et al (2023) examined the sociodemographic status of Indigenous and non-Indigenous children in Australia and its association with toothbrushing frequency. Their findings suggest that, while sociodemographic status is associated with lower toothbrushing frequency in non-Indigenous children, this was not the case with Indigenous children.…”
mentioning
confidence: 99%
“…Las desigualdades socioeconómicas en el cepillado dental fueron más visibles en los niños no indígenas. Estos resultados beneficiarán al incremento de intervenciones necesarias para la sociedad, y ayudara a mejorar el buen uso de la higiene oral en niños, tanto indígenas, como no indígenas 3 .…”
Section: Introductionunclassified